Cold-knife conisation and large loop excision of transformation zone significantly increase the risk for spontaneous preterm birth: a population-based cohort study. (August 2016) - Jančar, Nina; Mihevc Ponikvar, Barbara; Tomšič, Sonja
Abstract: Objectives: Our aim was to explore the association between cold-knife conisation and large loop excision of transformation zone (LLETZ) with spontaneous preterm birth in a large 10-year national sample. We wanted to explore further the association of these procedures with preterm birth according to gestation. Study design: We conducted a population based retrospective cohort study, using data from national Medical Birth Registry. The study population consisted of all women giving birth to singletons in the period 2003–2012 in Slovenia, excluding all induced labors and elective cesarean sections before 37 weeks of gestation ( N = 192 730). We compared the prevalence of spontaneous preterm births (before 28 weeks, before 32 weeks, before 34 weeks and before 37 weeks of gestation) in women with cold-knife conisation or LLETZ compared to women without history of conisation, calculating odds ratios (OR), adjusted for potential confounders. Chi-square test was used for descriptive analysis. Logistic regression analyses were performed to estimate crude odds ratio (OR) and adjusted odds ratio (aOR) and their 95% confidence intervals (95% CI) with two-sided probability ( p ) values. Results: A total of 8420 (4.4%) women had a preterm birth before 37 weeks of gestation, 2250 (1.2%) before 34 weeks of gestation, 1333 (0.7%) before 32 weeks of gestation and 603 (0.3%) before 28 weeks of gestation. A total of 4580 (2.4%) women had some type of conisation in their medical history: 2083 (1.1%) had cold-knife conisation and 2498 (1.3%) had LLETZ. In women with history of cold-knife conisation, the adjusted OR for preterm birth before 37 weeks of gestation was 3.13 (95% CI; 2.74–3.57) and for preterm birth before 28 weeks of gestation 5.96 (95% CI; 4.3–8.3). In women with history of LLETZ, the adjusted OR was 1.95 (95% CI; 1.68–2.25) and 2.88 (95% CI; 1.87–4.43), respectively. Conclusions: Women with cervical excision procedure of any kind have significantly increased odds for preterm birth, especially for preterm birth before 28 weeks and before 32 weeks of gestation.